PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT PENGGUNA BUS RAPID TRANSIT (BRT) DI KOTA SEMARANG - Saraswati, Maria Tika; Lestari, Hesti; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The background of this research is the many complaints of the public in using Bus Rapid Transit (BRT) Semarang. The purpose of this study is to determine and examine the effect of service quality on community satisfaction using Bus Rapid Transit (BRT) in Semarang City. The research method used is quantitative explanatory, with a research sample of 100. Sampling techniques using Probability Sampling techniques, especially using Simple Random Sampling techniques. The analysis techniques in this study are Validity test, Reliability test, Kendall Tau Correlation, and Determination Coefficient. The results showed that the quality of service to community satisfaction had a correlation of 0,316, with a significance level of 0.01. The value of the contribution of service quality to community satisfaction is 9.98%, so there are 90.02% of other variables that affect the variable of community satisfaction outside of the service quality variable. Based on these results, it can be concluded that there is an influence between the quality of service to community satisfaction of the community of Bus Rapid Transit (BRT) users in Semarang City. The advice given is to provide education or supply to each employee and continue to develop the facilities and infrastructure of BRT Trans Semarang